Prevalence and correlates of diabetes mellitus in Uganda: a population-based national survey - Bahendeka, Silver; Wesonga, Ronald; Mutungi, Gerald; Muwonge, James; Neema, Stella; Guwatudde, David (Tropical Medicine & International Health, 2016)
We analysed fasting blood glucose (FBG) and other data collected as part of a population-based nationwide non-communicable disease risk factor survey, to estimate the prevalence of impaired fasting glycaemia (IFG) and diabetes mellitus and to identify associated factors in Uganda. methods The nationwide cross-sectional survey was conducted between April and July 2014. Participants were adults aged 18–69 years. A multistage stratified sample design was used to produce a national representative sample. Fasting capillary glucose was measured to estimate glycaemia. Data were managed with WHO e-STEPs software and Epi Info. Stata survey procedures were used to account for the sampling design, and sampling weights were used to account for differential probability of selection between strata. results Of the 3689 participants, 1467 (39.8%) were males, and 2713 (73.5%) resided in the rural areas. The mean age was 35.1 years (standard deviation = 12.6) for males and 35.8 years (13.2) for females. The overall prevalence of IFG was 2.0% (95% confidence interval (CI) = 1.5–2.5%), whereas that of diabetes mellitus was 1.4% (95% CI 0.9–1.9%). The prevalence of IFG was 2.1% (95% CI 1.3–2.9%) among males and 1.9% (95% CI 1.3–2.6%) among females, whereas that of diabetes mellitus was 1.6% (95% CI 0.8–2.6%) and 1.1% (95% CI 0.6–1.7%), respectively. The prevalence of IFG was 2.6% (95% CI 1.4–3.8%) among urban and 1.9% (95% CI 1.3–2.4%) among rural residents, whereas that of diabetes mellitus was 2.7% (95% CI 1.4–4.1) and 1.0% (95% 0.5–1.6%), respectively. The majority of participants identified with hyperglycaemia (90.5% IFG and 48.9% diabetes) were not aware of their hyperglycaemic status. Factors associated with IFG were region of residence, body mass index and total cholesterol; factors associated with diabetes mellitus were age, sex, household floor finish and abdominal obesity. conclusion The prevalence of IFG and of diabetes mellitus is low in the Ugandan population, providing an opportunity for the prevention of diabetes. The majority of persons with hyperglycaemia were not aware of their hyperglycaemic status, which implies a likelihood of presenting late with complications.
Keywords: Diabetes mellitus; Non-communicable diseases; Chronic disease epidemiology; Uganda